Penggunaan Media Pembelajaran Power Point Untuk Meningkatkan Minat Belajar Sejarah Siswa Pasca Pembelajaran Daring (COVID-19) - Saputro, Toni Nugroho; Prakoso, Yusuf Andre; Rosanawati, I Made Ratih (Universitas Veteran Bangun Nusantara, 2023)
This research aims to better understand student’s situation after online study due to Covid-19 pandemic and how to deal the problem that arise from it. This reserch uses observation, interview, and literature study to collect data, interpret the result, and find the solution to solve the problem dicoverd during the research. The result of this research showed that online study had caused student to lose interest in History Lesson and made student to heavily rely in gadget (smartphone in particular) to solve problems, answer questions, and used as reference for any school work. After the use of media such as Power Pointthat contained illustration and summary of each subject of History Lesson that stimulate student’s attention and imagination, interest in History Lesson improved. Based on this research it can be concluded that the use of media in History Lesson could stimulate student’s interest and further improve understanding in subject matter. It is also noted that student’s dependence on gadget had risen and while the use of technology in education is inevitable, dependence and misuse could instead harm the student themselves and thus further study and regulation must be done in order to ensure the quality of education and student’s growth and future.